Cellulose and JbKOBITO 1 mediate the resistance of NaHCO3-tolerant chlorella to saline-alkali stress - Qiu, Jiale; Zhang, Jie; Zhao, Huihui; Wu, Cuiping; Jin, Caoliang; Hu, Xiangdong; Li, Jian; Cao, Xiuling; Liu, Shenkui; Jin, Xuejiao (Frontiers in Microbiology, 2023)
Carbonate stress has profound impacts on both agricultural and industrial production. Although a number of salinity-tolerant genes have been reported and applied in plants, there is a lack of research on the role of cell wall-related genes in resistance to carbonate. Likewise, in industry, current strategies have not been able to more effectively address the conflict between stress-induced microalgal biofuel accumulation and microalgal growth inhibition. It is of great significance to study the adaptation mechanism of carbonate-tolerant organisms and to explore related genes for future genetic modification. In this study, the role of the cell wall in the NaHCO3-tolerant chlorella JB17 was investigated. We found that JB17 possesses a relatively thick cell wall with a thickness of 300-600 nm, which is much higher than that of the control chlorella with a thickness of about 100 nm. Determination of the cell wall polysaccharide fractions showed that the cellulose content in the JB17 cell wall increased by 10.48% after NaHCO3 treatment, and the decrease in cellulose levels by cellulase digestion inhibited its resistance to NaHCO3. Moreover, the saccharide metabolome revealed that glucose, rhamnose, and trehalose levels were higher in JB17, especially rhamnose and trehalose, which were almost 40 times higher than in control chlorella. Gene expression detection identified an upregulated expressed gene after NaHCO3 treatment, JbKOBITO1, overexpression of which could improve the NaHCO3 tolerance of Chlamydomonas reinhardtii. As it encodes a glycosyltransferaselike protein that is involved in cellulose synthesis, the strong tolerance of JB17 to NaHCO3 may be partly due to the up-regulated expression of JbKOBITO 1 and JbKOBITO 1-mediated cellulose accumulation. The above results revealed a critical role of cellulose in the NaHCO3 resistance of JB17, and the identified NaHCO3-tolerance gene will provide genetic resources for crop breeding in salinealkali soils and for genetic modification of microalgae for biofuel production.